Analisis Risiko Produksi Peternakan Ayam Petelur di Desa Sumberbendo Kecamatan Pucanglaban Kabupaten Tulungagung - Yusuf Toriqfai; Siswahyudianto Siswahyudianto (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2022)
Risk analysis can be used by companies to identify possible risks faced and be able to overcome the emergence of risks that occur in the company. Once the source of risk is known, the company can implement the right risk strategy and produce something that allows the company to achieve its targets optimally. Therefore, the risks faced by business actors can certainly be overcome and the losses that occur can be minimized. The purpose of this study was to be able to know and understand how to minimize the risk and even overcome the risk of laying hens in Sumberbendo Village, Pucanglaban District, Tulungagung Regency. The research method uses descriptive qualitative data collection techniques in the form of interviews and observations. The results of the study explain that the sources of risk for laying hens in Sumberbendo Village, Pucanglaban District, Tulungagung Regency are in the form of chicken seeds, cleanliness, feed, care, weather, lack of accuracy in care and lack of knowledge about laying hens. The production strategy applied is to pay attention to internal and external factors in maintaining and caring for laying hens so that the risks that occur can be overcome so as to produce maximum production.